2013
DOI: 10.1089/jwh.2011.3186
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Relevance of Self-Reported Premenstrual Worsening of Depressive Symptoms in the Management of Depressed Outpatients: A STAR*D Report

Abstract: Objective: To determine the incidence, clinical and demographic correlates, and relationship to treatment outcome of self-reported premenstrual exacerbation of depressive symptoms in premenopausal women with major depressive disorder who are receiving antidepressant medication. Method: This post-hoc analysis used clinical trial data from treatment-seeking, premenopausal, adult female outpatients with major depression who were not using hormonal contraceptives. For this report, citalopram was used as the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The majority of women with MDD experience worsening of depressive symptoms in the luteal phase of the menstrual cycle. 29 Baseline and endpoint assessments of mood may be confounded by premenstrual mood exacerbation, with potential impact on study results. It is plausible that luteal phase worsening could complicate the interpretation of primary outcome data in MDD trials if it is not included in statistical modeling, even in randomized trials.…”
Section: Proposal For Methodological Advancementmentioning
confidence: 99%
“…The majority of women with MDD experience worsening of depressive symptoms in the luteal phase of the menstrual cycle. 29 Baseline and endpoint assessments of mood may be confounded by premenstrual mood exacerbation, with potential impact on study results. It is plausible that luteal phase worsening could complicate the interpretation of primary outcome data in MDD trials if it is not included in statistical modeling, even in randomized trials.…”
Section: Proposal For Methodological Advancementmentioning
confidence: 99%
“…Premenstrual exacerbation of depression has been linked in several studies to shorter time to relapse (Haley et al, 2013). …”
Section: Sex Differences In Mood Disordersmentioning
confidence: 99%
“…For many women, severity of symptoms of existing depression increases in the premenstrual phase [37]. In data from the STAR*D trial, 66% of women reported premenstrual exacerbations in their symptoms [38]. Of note, this was associated with longer depressive episodes and shorter latency to relapse.…”
Section: Humansmentioning
confidence: 99%